Autoimmune pancreatitis/IgG4-associated cholangitis and primary sclerosing cholangitis--overlapping or separate diseases? - Webster, G; Pereira, S; Chapman, R (2009)
Autoimmune pancreatitis is a recently described fibroinflammatory disease which is characterised by raised serum levels of IgG4 (in >70% of cases), and an IgG4-positive lymphoplasmacytic tissue infiltrate. A favourable and rapid clinical response to oral steroid therapy is often seen. Biliary involvement is common, and the term IgG4-associated cholangitis has recently been coined. The cholangiographic appearances of IgG4-associated cholangitis and primary sclerosing cholangitis can be difficult to differentiate. Moreover, raised levels of serum IgG4 have been recently found in 9% of patients with primary sclerosing cholangitis (a much higher frequency than for other gastrointestinal diseases), and those with raised levels appear to progress more rapidly to liver failure. Here we review the similarities and differences between the biliary disease in autoimmune pancreatitis and primary sclerosing cholangitis, and address the issue of disease overlap. Improvements in understanding the relationship between these conditions might lead to an enhanced understanding of the aetiopathogenesis, and improved treatment of both conditions.